Clinical Review of Ocular Traumas Resulting in Enucleation or Evisceration in a Tertiary Eye Care Center in Hungary - Gábor Tóth; Milán Tamás Pluzsik; Béla Csákány; Gábor László Sándor; Olga Lukáts; Zoltán Zsolt Nagy; Nóra Szentmáry (Journal of Ophthalmology)
Purpose. To analyse the demographic and clinical characteristics of ocular traumas resulting in enucleation/evisceration in a large tertiary referral center in a developed country (Hungary) over a period of 15 years. Patients and Methods. A retrospective review of enucleated/eviscerated eyes that underwent surgery between 2006 and 2020 at the Department of Ophthalmology of Semmelweis University, Budapest, Hungary, due to ocular trauma as the primary indication for enucleation/evisceration. For each subject, clinical history, B-scan ultrasound report, and histopathology results were reviewed. Results. There were 124 enucleated/eviscerated eyes from 124 patients (91 males (73.4%)). The mean age at the time of trauma was 37.3 ± 26.0 years while the mean age at the time of enucleation/evisceration was 46.9 ± 20.3 years. The main clinical diagnoses after ocular trauma were open globe injury (n = 96; 77.4%), ocular burns (n = 6; 4.8%), traumatic optic neuropathy (n = 4; 3.2%), bulbar avulsion (n = 3; 2.4%), traumatic cataract (n = 2; 1.6%), retinal ablation (n = 1; 0.8%), and traumatic carotid-cavernous fistula (n = 1; 0.8%). Among the 124 patients, 98 (79.0%) underwent enucleation and 26 (21.0%) evisceration. Patients who underwent primary enucleation/evisceration (n = 24 19.4%) were significantly older at the time of the injury (57.7 ± 22.7 years) than people who underwent secondary eye removal (32.4 ± 24.4 years) (p<0.0001). The mean time interval between trauma and enucleation/evisceration was 114.9 ± 163.5 months. The main clinical indications for anophthalmic surgery were atrophia/phthisis bulbi (n = 56, 45.2%), acute trauma (n = 25, 20.2%), painful blind eye due to glaucoma (n = 17, 13.7%), endophthalmitis (n = 10, 8.1%), and cosmetic reasons (n = 7, 5.6%). One patient (0.8%) had sympathetic ophthalmia. Conclusions. Primary enucleation/evisceration was performed in one-fifth of all ocular trauma-related anophthalmic surgeries in our tertiary eye care center with enucleation being the most common procedure. Atrophia/phthisis bulbi was the most frequent immediate clinical indication for enucleation/evisceration.